Characterisation of recycled plastics for automotive radar applications at 77 GHz - Ameerudeen, Mohamed Azad; Nourjoo, Mohammad (My University, 2024)
This work investigates the potential of various recycled plastic materials for use in bumper areas which are in closer proximity to automotive radar systems operating at 77 GHz. The study focuses on both experimental and analytical calculation approaches to assess the electromagnetic properties of these materials, specifically focusing on their complex permittivity and loss tangent characteristics at 77 GHz. For this purpose, a quasi-optical measurement setup which utilises metallic reflective mirrors to narrow and collimate the beam of waves produced by WR12 frequency extenders in the 65-90 GHz range is used. The S-parameters measured by the Vector Network Analyzer (VNA) of the samples are utilised to calculate the complex refractive index. This procedure allows for the determination of the permittivity and loss tangent for each specific sample material. To ensure the robustness of the calculation method, the known permittivity and loss tangent values at 77 GHz from a reference non-recycled material provided by the supplier are utilised to calculate theoretical S-parameters, which are then employed in the same method to re-evaluate the permittivity and loss tangent. This process enables a direct comparison with the initial VNA-derived results. This round-trip verification process confirms the reliability of the calculation method used in the analysis. From the analysis of all test materials, a particular recycled plastic material is chosen, suggesting its potential suitability for use in automotive bumper production. Overall, this research offers significant insights into the development of radar-compatible recycled plastics for bumper design and manufacturing.
Keywords: Automotive radar, recycled plastics, metallic reflective mirrors, S-parameters, Quasi-optical technique, refractive index, permittivity and loss tangent